Становлення нової української школи: якими повинні бути сучасні реформи освітньої галузі - Дяченко, Світлана Анатоліївна (Київський національний університет імені Тараса Шевченка, 2018)
Ідеться про реформування сучасної освітньої галузі, зокрема і про зміни, які відбувалися в літературній освіті в різні часи її становлення. Зосереджено увагу на ключових моментах в історії розвитку літературної освіти, аби на сучасному етапі засоби літератури мали позитивний виховний вплив на підростаюче покоління.

The article deals with the reform of the modern educational sphere, and the changes that took place in literary education at different times of its development, in particular. The author focuses on the key points in the history of the development of literary education, so that the means of literature positively affect the younger generation's education at the present stage. Historically, literary education in Ukrainian schools has undergone a thorny path while forming and developing. The new Ukrainian school, whose main goal was the upbringing of the younger generation, has become operative since the end of 1917. And although there was not yet a single curriculum and program, the most important means of realizing the main school goal was the literature itself. At that time, literature was the center of attention, the core of the curriculum, while the Ukrainian language and literature at the Ukrainian schools of that time were the subjects that claimed the largest share of academic hours per week. The academic content of modern literary education is a painful issue that is to be discussed specifically, and the reform of the educational sector should touch upon it precisely. The analysis of the modern program in Ukrainian literature proves that it is far from being ideal and requires careful revision from scientific, methodological and psychological points of view. It was back in the first half of the nineteenth century that Taras Shevchenko convincingly argued that the weighty instrument of education and culture should be an artistic word. his formula is remembered today as well: the interests of ordinary people should be guarded by the word, which would make them see life's falsehood and teach the workers to fight against social evil. At his time, Ivan Franko was keen on filling school curricula and textbooks with Ukrainian literature. He deeply analysed and sharply criticised the programs that were officially imposed on the then school. He considered them the main reason for the students' reluctance to learn, contempt of the Ukrainian language, literature and history, indicating that this reason is inherent in the school system. He undeniably believed that the works children study at school should be truly literary. Ivan Ogienko saw Ukrainian literature as a treasury of national pride and an important educational tool. The teacher substantiated the provisions on the need to educate the youth of that time basing on the traditions of the Ukrainian Cossacks, on the best examples of literary works, on the heroic deeds of our Motherland's defenders. Ohiyenko was convinced that the responsibility of every Ukrainian intellectual patriot, who is to be formed by the school (above all by the means of the Ukrainian artistic word), is primarily to increase the cultural level of the entire Ukrainian people, the struggle for its spiritual revival, and the construction of an independent state. The author of the article asserts that the reform of the modern Ukrainian school should start first of all with the academic content of literary education, not with the idea of full integration of independent and equal school subjects. The idea of introducing integrated lessons into the educational process as the newest types of Ukrainian literature lessons is very good, worthy of attention and is now being successfully implemented by the best teachers of Ukraine. The author of the article emphasizes that the integration in such lessons is not full, but partial. Partial integration, which is achieved by including some interesting materials that offer the possibility to learn about a phenomenon or a concept from different perspectives and to achieve the integrity of knowledge, provides information enrichment of perception, thinking and feelings of the students. The thoughtless reformation of the educational system in the 1920-1930s, the search for new optimal forms of organization of the educational process that was undertaken by the heads of departments led to the fact that the subject, classroom teaching system was eliminated as unfit for use in the then schools, and literature lost its leading role as the main educational and educational object, becoming an illustrative material for social phenomena. In conclusion, the author expresses the hope that the passion for the pedagogical experiments of other countries in the modern Ukrainian school and the introduction of ideas for the full integration of school subjects will not create insensibility in the formation of knowledge and skills of students, will not ignore the educational role of literature and will not lead to the leveling of the specifics of the study of Ukrainian literature (as well as other school subjects) as a unique phenomenon and spiritual wealth of Ukrainians.
The development of the new ukrainian school: the requisite modern reforms of the educational sector
Keywords: the reform of the educational branch; the filling of school programs in literature; the history of school literary education; integrated literature lessons; реформа освітньої галузі; наповнення шкільних програм із літератури; історія шкільної літературної освіти; інтегровані уроки з літератури